1) Производная : ║(x+2)(-3)-(4-3x)(1)║÷(x+2)²= -10/(x+2)²
2) Производная:║6cos18x-tg5x)×0 +6sin18x×18+ (1/cos²5x)×5║÷(6cos18x- tg5x)² =║108sin18x +5/cos²5x║÷(6cos18x-tg5x)²
3) Производная: 6×3 -0,5(8x+7)×8 = 18-4x+3,5=14,5-4x
Вертикальные двойные использованы как квадратные скобки.
Желаю успеха!
Пошаговое объяснение:
1) Производная : ║(x+2)(-3)-(4-3x)(1)║÷(x+2)²= -10/(x+2)²
2) Производная:║6cos18x-tg5x)×0 +6sin18x×18+ (1/cos²5x)×5║÷(6cos18x- tg5x)² =║108sin18x +5/cos²5x║÷(6cos18x-tg5x)²
3) Производная: 6×3 -0,5(8x+7)×8 = 18-4x+3,5=14,5-4x
Вертикальные двойные использованы как квадратные скобки.
Желаю успеха!
Пошаговое объяснение: